Maternal, perinatal, and socio-demographic factors associated with childhood disabilities: evidence from a cross-sectional study in Rajshahi, Bangladesh - Al Kafi, Abdullah; Shoshi, Belona Nasrin (International Journal of Research in Medical Sciences, 2026)
Background: Childhood disability pertains to an important public health issue with a complex etiology which includes genetic, biological and environmental factors. However credible prevalence information about disability profiles and its associated factors are scarce, especially outside the major urban areas of Bangladesh. This study was designed to determine the prevalences of common disabilities among children in Rajshahi and their relationship with maternal, prenatal, and socio-demographic factors. Methods: A cross-sectional study was conducted among 120 children attending Islami Bank Medical College and Hospital in Rajshahi, selected through purposive sampling. Data were collected via face-to-face interviews with mothers/guardians using a structured questionnaire. Descriptive statistics and chi-square tests were employed to analyze the distribution of disabilities and their associations with risk factors using SPSS version 22. Result: This was a descriptive cross-sectional study done in the Department of Medicine, Islami Medical College and Hospital, Rajshahi, Bangladesh, July 2024 to June 2025. A purposive sample of 120 disabled children who visited the hospital in the study period were recruited. Relevant data were gathered through personal interview of mothers or caretakers, employing a predesigned and pretested semi-structured questionnaire. All disabled children then attending the institute during the study period were already included, and no one declined to participate. Conclusion: The results highlight a multi-etiology of childhood disability in the study area, and underscore the contribution of perinatal events, maternal age and family disposition to its etiology. Integrated public health management strategies that address issues such as lack of prenatal care, early screening, parental awareness, and inclusive community-based support are urgently needed to reduce disability risks and improve quality of life of affected children.